Motivational factors of musical practice among UiTM music majors during COVID-19 pandemic / Braxter Chong Hong Liang and Hairun Alif Ariffin Hairun Anuar - Chong, Braxter Hong Liang; Hairun Anuar, Hairun Alif Ariffin (2022)
The sudden change of established practice patterns and absence of required infrastructure such as practice rooms has caused a challenge to the practice routine of music students. The lack of face-to-face interactions with audiences through concerts and performances, as well as online and asynchronous instrumental and vocal lessons may have resulted in a reduction in or stagnation of confidence and motivation among music students with potentially negative effects for musical practises (Nusseck, M., & Spahn, C. 2021). Although there have been studies on the topic of motivational factors, only a number of them were focused on musical practice during the pandemic. Therefore, the aim of this study is to find out the commitment level and motivational factors in musical practice of the UiTM Faculty of Music instrumental students during the pandemic. The data has explored 58 UiTM music students from three departments that involve instruments study in their current and past semester. Throughout the data collected from the survey, the findings revealed that overall commitment level of UiTM music students in musical practice during the COVID-19 lockdown were moderate. This study was not comparative analysis, so the findings were inefficient to compare the commitment level between before and after the COVID-19 lockdown. In addition, the finding revealed the motivational factors that involved UiTM music students for their musical practice. Our discussion has covered and interpreted the data collected to have a clear conclusion for this study. This study will benefit the music education field to understand motivational factors involved in musical practice. Lastly, some recommendations have been presented for future research to study the comparison between during the lockdown and after.